Classical and novel strategies to develop a Shigella glycoconjugate vaccine: from concept to efficacy in human. Issue 6 (3rd June 2019) - Barel, Louis-Antoine; Mulard, Laurence A.
ABSTRACT: Shigella are gram-negative bacteria that cause severe diarrhea and dysentery, with a high level of antimicrobial resistance. Disease-induced protection against reinfection in Shigella -endemic areas provides convincing evidence on the feasibility of a vaccine and on the importance of Shigella lipopolysaccharides as targets of the host humoral protective immune response against disease. This article provides an overview of the original and current strategies toward the development of a Shigella glycan-protein conjugate vaccine that would cover the most commonly detected strains. Going beyond pioneering "lattice"-type polysaccharide-protein conjugates, progress, and challenges are addressed with focus on promising alternatives, which have reached phases I and II clinical trial. Glycoengineered bioconjugates and "sun"-type conjugates featuring well-defined synthetic carbohydrate antigens are discussed with insights on the molecular parameters governing the rational design of a cost-effective glycoconjugate vaccine efficacious in preventing diseases caused by Shigella in the most at risk populations, young children living in endemic areas.